Modeling the effect of hypothetical chlorine leakage from Malay-Sino Chemical Industries using ALOHA software and development of an emergency evacuation route around Teluk Kalong industrial area - Law, Woonphui Phui; Gimbun, Jolius (IOP Publishing Ltd, 2020)
Malay-Sino Chemical Industries in Teluk Kalong is the largest chlor-alkali manufacturer in Malaysia, which may potentially affect the safety of plant workers and nearby residential area in the event accidental chlorine leakage. The dispersion of a hypothetical chlorine leakage from Malay-Sino Chemical Industries in Teluk Kalong industrial area was modelled using ALOHA. The effect of different wind direction, wind speed and time in the meteorological mesoscale area was evaluated. The wind speed ranging from 1.55 to 11.1 m/s obtained from a local weather station was considered. Heavy gas dispersion model was used to determine the concentration of chlorine plume within the area of concern. The leakage rate was set at 702 kg/h. The result showed that the residential area R5 (Kampung Bukit Kuang, and Kampung Sungai Terjun) is affected by the plume dispersed by northern wind at night. A greater hazard zone can be formed under the wind speed below 1.55 m/s. A suitable safety evacuation routes were proposed to reduce the risk of exposure to hazardous gas. Finding from this work is useful to understand the risk of hazardous gas dispersion around Teluk Kalong industrial area.